A study on the Cr(VI) removal from aqueous solutions by steel wool - Özer, Ahmet; Altundoğan, Hamdi Soner; Erdem, Mehmet; Tümen, Fikret (My University, 1997)
The reduction of Cr(VI) by steel wool and the precipitation of reduced chromium by CaCO(3) powder and NaOH solution were investigated in continuous and batch systems, respectively. The effects of acid and initial Cr(VI) concentrations, volumetric rate and temperature of solution on Cr(VI) reduction were studied. The results showed that the reduction of Cr(VI), to a large extent, depended on, and increased with, acid concentration. The Cr(III) and iron ions in the reduced solution were completely precipitated by using NaOH solution at appropriate alkaline conditions. It was concluded that CaCO(3) powder could be used as a cheap precipitant for Cr(III) ions. But the iron ions in the reduced solution could not be fully removed by using this precipitant.
Makale - Bilimsel Dergi Makalesi - Çok Yazarlı
Keywords: Steel wool; Hexavalent chromium; Reduction; Precipitation